2005
DOI: 10.1137/s0097539702411381
|View full text |Cite
|
Sign up to set email alerts
|

Orderly Spanning Trees with Applications

Abstract: We introduce and study the {\em orderly spanning trees} of plane graphs. This algorithmic tool generalizes {\em canonical orderings}, which exist only for triconnected plane graphs. Although not every plane graph admits an orderly spanning tree, we provide an algorithm to compute an {\em orderly pair} for any connected planar graph $G$, consisting of a plane graph $H$ of $G$, and an orderly spanning tree of $H$. We also present several applications of orderly spanning trees: (1) a new constructive proof for Sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 52 publications
0
86
0
Order By: Relevance
“…As was shown in [4], we can always obtain such drawings with O(n 2 ) area. Here we show that this bound is tight: there exist outerplane graphs that require Ω(n 2 ) area.…”
Section: Mosaic Drawings Without Channelsmentioning
confidence: 75%
See 2 more Smart Citations
“…As was shown in [4], we can always obtain such drawings with O(n 2 ) area. Here we show that this bound is tight: there exist outerplane graphs that require Ω(n 2 ) area.…”
Section: Mosaic Drawings Without Channelsmentioning
confidence: 75%
“…More specifically, there exist outerplane graphs with k ears, such that any mosaic drawing of these graphs has either Ω(n 2 /k 2 ) area or total channel complexity Ω(k). This bound is tight, since the algorithm by Chiang et al [4] can be used to construct mosaic drawings without channels in O(n 2 ) area. In Section 4 we consider straight channels.…”
Section: Simple Mosaic Drawingsmentioning
confidence: 97%
See 1 more Smart Citation
“…-Balanced parentheses Chuang et al 1998;He et al 1999;Chiang et al 2005;Munro and Rao 2004;Bonichon et al 2006], a folklore encoding consisting of a balanced string of parentheses representing the counterclockwise depth-first traversal of T , where an open (respectively, closed) parenthesis denotes a descending (respectively, ascending) edge traversal. For technical reason, one usually adds a pair of enclosing parentheses to the above 2n − 2 parentheses, resulting in a representation consisting of 2n parentheses.…”
Section: Dfudsmentioning
confidence: 99%
“…Munro, Raman, and Rao showed an o(n)-bit auxiliary string to support O(1)-time query for leaf-rank, leaf-select, and leaf-size. Chiang, Lin, and Lu [Chiang et al 2005] showed an o(n)-bit auxiliary string to support O(1)-time degree query. Munro and Rao [Munro and Rao 2004] further gave an o(n)-bit auxiliary string to support O(1)-time level-ancestor query.…”
Section: Dfudsmentioning
confidence: 99%